Molecular Docking and Dynamics Simulation for Searching Anti-Cancer Compounds of Piperlongumine Derivatives that Have Potential as an Inhibitor Against MAO-B (Monoamine Oxidase B) - Agus Salim; Raden Rara Fadhila Kirana Nugrahani; Yolanda Amalia; Suwardi Suwardi (Universitas Negeri Yogyakarta, 2023)
The docking of the piperlongumine molecule and its derivatives has been carried out to find molecules that have the potential as anti-cancer. A total of 18 ligands were docked to the 2v5z protein using the autodock4 and autodock vina programs. The binding energies of piperlongumine and piperlongumine derivatives [R1 = CH3 and R2 = H] were -8.6 kcal/mol and -9.3 kcal/mol, respectively. Based on molecular dynamics simulations, the hydrogen bond interaction fraction was dominated by GLN 206 residue in both the SAG (88%) and piperlongumine derivatives ((R1=CH3, R2 = H)(93%) ligand, for this reason, this piperlongumine derivative molecule is predicted to have potential as MAO B inhibitor.